Perlindungan Hukum Terhadap Pengungsi Lintas Batas Negara Di Indonesia - Reinier Sukarnolus Dimitri Sitanala (Faculty of Law, Universitas Pattimura, 2018)
The protection of these cross-border refugees has already been regulated in international law, namely the Geneva Convention 1951 and the 1967 Protocol, but Indonesia is not a party to ratify the Convention. So far Indonesia has only dealt with the problem of cross-border refugees from a priesthood perspective. This resulted in many violated human rights. Indonesia as a transit country must cooperate with the country of origin, destination country and UNHCR to overcome and provide protection for cross-border refugees. The role taken is based on humanity's consideration of the suffering of cross-border refugees and the protection of Human Rights.